Is Ontario Moving to Provincial Negotiation of Teaching Contracts? - Anne L. Jefferson (Educational Considerations, 2008)
In Canada, the statutes governing public school teachers’ collective bargaining are a combination of the provincial Labour Relations Act or Code and the respective provincial Education/School/Public Schools Act.
Keywords: provincial; Labour Relations Act or Code; school; teachers; Ontario elementary school teaching federation (OESTF); Ontario secondary school teaching federation (OSSTF).